Sonification of geometry - Teo, Han Hua (Nanyang Technological University, 2023)
There has been a substantial amount of research put into training neural networks that are used to predict the sounds of arbitrary 3D mesh objects. Each of these different neural networks all have their various ways of preprocessing these 3D mesh objects so that it can help to accelerate the process of training the neural network model. As such, this project investigates whether it is feasible to train such modal sound neural network models without the preprocessing.